Modalitas Petani Kopi Panorama Dalam Hubungan Kerja Sosial Produksi Dengan Perhutani (Studi Pada Kelompok Petani Panorama Dalam Bekerjasama Dengan Perhutani Kecamatan Dampit Kabupaten Malang) - Wisadirana, Darsono; Amalia A, Diyah Ayu; Indah P S, Qurnia; Amalia, Bawon Rizki; H P, Vildan Cresanda (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This research aims to analyze in more depth the modalities of Panorama Coffee farmers in their working relationship with Perhutani in the Dampit Region. The research approach is qualitative with a case study method. This research will analyze the form of cooperation carried out between Panorama coffee farmers and Perhutani, identify factors that become obstacles in the working relationship between coffee farmers and Perhutani, identify the rights and obligations imposed on collaborating parties, and identify the legal form of work agreements. the same social production partnership between coffee farmers and forestry. The results of this research are that the Panorama Coffee Farmers Group has social, cultural, economic and symbolic capital in its working relationship with Perhutani. The form of collaboration between Perhutani and Farmer Groups is the business of utilizing wood forest products in plantation forests, plant development, planting land under Standing (PLDT), Silvopastura (livestock farming) and Ecotourism and Nature Tourism Utilization Business. Some of the obstacles to the working relationship between Perhutani and the Panorama Coffee Farmers Group are the availability of capital for coffee farmers, the area of land borrowed by farmers from Perhutani which also affects coffee production, the cost of fertilizers and pesticides, and the level of knowledge possessed by farmers.